O ¿QUÉ SERÁ THAM? EVALUACIÓN / INTERVENE CONOCIMIENTOS METALINGÜÍSTICOS - Figueira, Ana Paula Mendes Correia Couceiro (2020)
We intend to operationalize the construct metalinguistic awareness and present three tests (THAMs, tests of metalinguistic abilities), tests or resources that allow to analyze this competence. Given that we consider this capacity important and usable from childhood. The proposal offers tools for three different age groups: for children, THAM-1, for adolescents, THAM-2 and for adults, THAM-3. These resources are adaptations to the European Portuguese of MAT's, original in Italian version, by internationally recognized authors, with versions in several languages, worldwide disseminated, even by way of a project European, MATEL. At the national level, they are already in circulation, through the publication of a book, and there are several ongoing investigations.